Systematic review with meta‐analysis: The effects of non‐steroidal anti‐inflammatory drugs and anti‐platelet therapy on the incidence and recurrence of hepatocellular carcinoma. Issue 4 (11th July 2021) - Tan, Regina Zi Hwei; Lockart, Ian; Abdel Shaheed, Christina; Danta, Mark
Summary: Background: Chemoprevention with NSAIDs, including aspirin, and anti‐platelet therapy (APT), has been suggested to reduce the incidence and recurrence of hepatocellular carcinoma (HCC). Aim: To determine by meta‐analysis whether NSAIDs and APT use affected HCC incidence, HCC recurrence and liver‐related mortality in at‐risk populations with chronic liver disease. Method: Electronic databases including Pubmed, Scopus, Medline, Embase and Cochrane Library were searched (from inception to 31 May 2021) for eligible studies evaluating the impacts of NSAID or APT use on HCC incidence, recurrence and mortality. Data on HCC incidence, recurrence, liver‐related mortality or bleeding complications had to be available. Studies were included if they evaluated adults with hepatitis B virus (HBV), hepatitis C virus (HCV), alcohol‐related liver disease (ALD) or nonalcoholic steatohepatitis that were administered at least one NSAID or APT for a defined period of time and were followed for at least 6 months. The primary outcome was HCC incidence. Secondary outcomes included: HCC recurrence, liver‐related mortality and bleeding complications. Data were pooled using a random effects model with hazard ratios (HRs) or odds ratio (OR), and 95% confidence intervals (CIs) presented. Results: Of 3773 articles screened, 19 studies were included, with a total of 147 283 participants. Aspirin use reduced the risk of HCC incidence (HR: 0.51, 95% CI: 0.36‐0.72); and improved liver‐related mortality (OR: 0.32, 95% CI: 0.15‐0.70), with a small increased risk of gastrointestinal bleeding events (OR: 1.32, 95% CI: 1.08‐1.94). With respect to HCC recurrence following treatment, analysis of all aspirin and NSAID treatment (including; aspirin only; non‐aspirin NSAIDs only; and combination NSAIDs groups) was associated with a decreased risk of HCC recurrence (HR: 0.80, 95% CI: 0.75‐0.86). By stratified analysis, only the non‐aspirin NSAID group showed significant risk reduction (HR: 0.73, 95% CI: 0.63‐0.84). Conclusion: The study supports the use of aspirin in at‐risk individuals to reduce the incidence of HCC and liver‐related mortality. HCC recurrence following treatment was lower with NSAID treatment. Abstract : Aspirin use significantly reduced the risk of HCC incidence (HR: 0.51, 95% CI: 0.36‐0.72); and improved liver‐related mortality (OR: 0.32, 95% CI: 0.15‐0.70), with a small increased risk of gastrointestinal bleeding events (OR: 1.32, 95% CI: 1.08‐1.94).